Midlands cadences: Narrative voices in the work of Alan Sillitoe. (November 2016) - Scott, Jeremy
This paper will examine excerpts from a range of Alan Sillitoe's prose fiction, Saturday Night and Sunday Morning (1958) and short stories from the collection The Loneliness of the Long-Distance Runner (1958), via a comparative exploration of the texts' representations of Midlands English demotic. The narrative discourse traces a link between the experience of the Midlands English working classes represented and the demotic language they speak; the narrators have voices redolent of registers rooted in 1950s English working-class life. The texts also contain different methods of representing their protagonists' consciousness through the demotic idiolects that they speak. Sillitoe's is a novelistic discourse which refuses to normalise itself to accord with the conventions of classic realism, and as such prefigures the ambitions of many contemporary writers who incline their narrative voices towards the oral – asserting the right of a character's dialect/idiolect to be the principal register of the narrative. The paper will demonstrate this thesis through the ideas of Bakhtin, and through an analytical taxonomy derived from literary stylistics. It aims to propose a model which can be used to analyse and explore any fiction which has been labelled as 'working-class', and asserts that such an approach leads to a more principled characterisation of working-class fiction (based on its use of language) than current literary-critical discussions based simply on cultural/social context and biography.